Local Wisdom and Spatial Management of Marine Resources: Erang Pakboya-boyang as a Model for Sustainable Environmental Practices - Hasriyanti Hasriyanti; Maisarah Munirah Latief; Nur Alifah; Titus Adeyemi Alonge; Ogunrinde Emmanuel Abiola (JAMBURA GEO EDUCATION JOURNAL, 2026)
The marine ecosystem faces escalating degradation from global pressures, but the local management of these resources remains deeply guided by traditional frameworks of religion and belief. This research examines how spiritual wisdom in Patorani culture contributes to marine resource management in Galesong Sub-district, Takalar Regency, located on the southern coast of South Sulawesi. Using an ethnographic approach, this qualitative study explores the role of ritual practices in the management of marine resources by Patorani fishermen. Data were collected through documentation, literature review, interviews, and observation. The findings highlight the series of rituals, such as pakdoangang (safety prayers), kasipalli (taboos), papasang (messages), and the use of pakkaja and balla-balla fishing gear, which form an imaginary dialogue with spiritual forces. The rituals are viewed as a spatial engagement between the fishermen and the Torani fish (flying fish) to ensure successful fishing. This study shows that these rituals embody spiritual wisdom in marine resource management, aligning traditional practices with sustainability. Future research is recommended to quantitatively measure the ecological impacts of these practices on fish stocks and conduct comparative studies with other indigenous maritime cultures to explore the adaptability of these principles in broader contexts